Zinc alkene coating still having long-term protection capability after being damaged and preparation method of zinc alkene coating
By using two-component structure and adhesion promoter in aqueous epoxy zinc-rich coatings, the problem of the existing water-based epoxy zinc-rich coatings decreased after damage is solved, the long-term protection ability and high adhesion of the coating are achieved, and the service life of the coating is extended.
Patent Information
- Application Number
- CN202411961743.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
The protection capacity of existing water-based epoxy zinc-rich coatings decreases after damage, resulting in a shortening of the service life of the coating, complex construction, dust pollution and other problems.
Two-component aqueous epoxy zinc olefin coating is used, and the hydrophilic polyamide curing agent is used as the carrier of zinc powder, and is pre-dispersed into zinc slurry, and cross-linked and cured with epoxy emulsion to increase adhesion accelerator to improve the adhesion between the coating and the substrate.
It still has long-term protection after damage, which significantly improves the corrosion resistance and corrosion spread of the coating, extends the service time of the coating, and reduces maintenance costs.
Smart Images

Figure BDA0005217338190000121 
Figure BDA0005217338190000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water-based coatings, and in particular provides a zinc-ene coating having long-term protective capability after being damaged and a preparation method thereof. Background Art
[0002] Solvent-based two-component epoxy zinc-rich coatings have good corrosion resistance and relatively mature market applications. They have always played an important role in fields with relatively high corrosion protection requirements such as bridges, chemical storage tanks, wind power, containers, and marine corrosion protection. Due to increasingly stringent environmental protection requirements, water-based epoxy zinc-rich coatings have replaced solvent-based epoxy zinc-rich coatings and have become an inevitable trend of development; water-soluble epoxy resins and solvent-based epoxy resins have great differences in curing mechanism. Solvent-based epoxy resins and solvent-based curing agents are evenly mixed to obtain a homogeneous system, so cross-linking and curing reactions can directly occur between molecules of solvent-based epoxy resins during curing. As the solvent gradually evaporates, the curing reaction gradually tends to be complete, forming a dense and uniform epoxy resin coating; while water-soluble epoxy resins are a two-phase system (organic phase and aqueous phase), and epoxy resins are dispersed in water in the form of emulsion particles, so whether solvent-based epoxy curing agents or water-soluble epoxy curing agents are used, the curing agent is mostly dispersed in one of the phases. The curing reaction first occurs in the emulsion microspheres, and then on the surface where the emulsion microspheres contact each other. In this way, the surface water solvent is more easily volatilized, which makes the surface cure quickly and plays an isolating role. In addition, due to the existence of capillary force, the lower layer of water solvent evaporates slowly, so the epoxy resin molecules and curing agent molecules between the lower emulsion microspheres are difficult to cross-link and react with each other to produce curing reactions, resulting in different curing degrees of each part. Therefore, the curing time is longer than that of solvent-based epoxy resin, which may also lead to incomplete curing. And it causes more water to be wrapped and adsorbed in the paint film. Therefore, in essence, the curing degree of water-soluble epoxy resin paint film is not as good as that of solvent-based, and the resin cross-linking density is relatively poor, resulting in relatively low overall anti-corrosion performance of the paint film; usually, most of the additives of solvent-based epoxy resins and water-based epoxy resins are not universal, and whether the additives suitable for solvent-based epoxy resins can play a corresponding role in curing for water-soluble epoxy resins cannot be expected to be inferred, but the anti-corrosion performance of the paint film can be improved by other means to make up for this deficiency, so that the anti-corrosion performance of the water-based paint film is equivalent to or even better than that of the solvent-based. Since zinc powder is relatively active and easily reacts with water, most commercially available water-based epoxy zinc-rich coatings are prepared with three components: coating + curing agent + zinc powder in three packages. Zinc powder is added and stirred evenly at the site of use before adding the curing agent. The water-based epoxy zinc-rich primer prepared by this method is complicated to construct and is not suitable for fast-paced, assembly-line coating production. It also has many disadvantages such as inconvenient construction, dust pollution, and zinc powder that cannot be used up and is easily oxidized. On the other hand, the water-based epoxy zinc-rich product system consists of a water-based epoxy emulsion, or a hydrophilic epoxy resin plus a hydrophilic polyamide curing agent plus zinc powder. It uses 100% liquid epoxy resin with a polyamide curing agent with an emulsifying function. Through the emulsifying function of polyamide, the liquid epoxy resin is emulsified and then diluted with water. This approach is relatively low in cost, but because the curing agent contains an emulsifier, the performance is relatively poor.And due to the presence of hydrophilic groups and emulsifiers, the water resistance and salt spray resistance of the coating will be greatly affected. Even if the commercially available water-based epoxy zinc-rich coating meets the rust technical indicators after the salt spray test after thousands of hours, its secondary adhesion after the salt spray test has been significantly reduced, that is, the ability to resist the spread of corrosion is weak. In the case of external pulling, the coating will be partially peeled off from the substrate. Objectively speaking, this situation will greatly affect the service life of the coating.
[0003] Therefore, it is an urgent problem to develop a zinc-ene coating that still has long-term protective capabilities after being damaged, so that the coating made with it has excellent corrosion resistance, especially excellent resistance to the spread of corrosion, can still provide excellent protection after the coating is damaged, extend the service life of the coating, reduce the number of repairs to the coating, and greatly reduce maintenance costs. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a zinc-ene coating having long-term protective capability after being damaged and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] On one hand, the present invention provides a zinc-ene coating having long-term protective capability after being damaged, comprising: component A and component B, wherein the mass ratio of component A to component B is 1:2.5-4, component A comprises epoxy resin emulsion, thickener, wetting agent, defoamer, anti-flash rust agent, deionized water and graphene dispersion, component B comprises curing agent, adhesion promoter, dispersant, defoamer, rheological additive, mica powder, active pigment, zinc powder and solvent, and component A comprises, by weight: 70-80 parts of epoxy resin emulsion; Thickener 0.2-0.6 parts; wetting agent 0.1-0.4 parts; defoamer 0.1-0.4 parts; anti-flash rust agent 0.1-0.4 parts; deionized water 2-12 parts; graphene dispersion 10-25 parts; component B, by weight, includes: curing agent 3-6 parts; dispersant 1-1.5 parts; defoamer 0.1-0.4 parts; rheological additive 0.2-0.6 parts; mica powder 2-3 parts; active pigment 4-10 parts; zinc powder 70-80 parts; adhesion promoter 1-2 parts; solvent 4-12 parts.
[0006] Preferably, the epoxy resin emulsion is one or more of an emulsion of an E-20 system, a self-emulsifying resin of an E-20 system, an emulsion of an E-51 system, and a self-emulsifying resin of an E-51 system; the thickener is one or more of cellulose, hydrophobic modified acrylate, and polyurethane; the wetting agent is one or more of a surfactant, a low molecular weight siloxane-type surfactant, a fluorocarbon surfactant, and an acetylene glycol.
[0007] Further preferably, the defoaming agent is one or more of natural oils and fats, polyether defoaming agents, high carbon alcohol defoaming agents, silicon defoaming agents, polyether modified silicon defoaming agents, and polysiloxane defoaming agents; the flash rust inhibitor is one or more of sodium nitrite, sodium molybdate, strontium chromate, metal organic chelates, and multifunctional phosphate chelates.
[0008] Further preferably, the graphene dispersion is one or more of single-layer graphene, multi-layer graphene, graphene oxide, hydrogenated graphene, and functionalized graphene.
[0009] More preferably, the adhesion promoter is one or more of a silane coupling agent, acetylacetone, and an organic-inorganic hybrid modified silane coupling agent.
[0010] More preferably, the active pigment is one or more of super phosphorus zinc white, natural ferrophosphorus powder, polymerized ferrophosphorus powder, and iron-titanium powder.
[0011] Further preferably, the curing agent is one or more of amidated polyamines, polyamides, and amine adducts; the dispersant is one or more of anionic, cationic, nonionic, electrically neutral, and polymeric; and the rheological additive is one or more of organic bentonite, clay, castor oil derivatives, fumed silica, modified hydrogenated castor oil, modified polyurea in N-methylpyrrolidone solution, and polyamide wax.
[0012] Further preferably, the mica powder is one or more of muscovite, sericite, and phlogopite with a mesh size between 100 mesh and 1500 mesh; the zinc powder is one or more of spherical zinc powder and flake zinc powder with a mesh size between 600 mesh and 1200 mesh and a purity of more than 95%; and the solvent is one or more of PM, DPM, PMA, and BCS.
[0013] The present invention also provides a method for preparing the zinc-ene coating having long-term protective capability after being damaged, comprising the following steps:
[0014] 1) Preparation of component A:
[0015] (1) According to the weight ratio, epoxy resin emulsion, defoamer, wetting agent, anti-rust agent, deionized water and graphene dispersion are fully mixed and stirred;
[0016] (2) adding a thickener to the mixture in step (1) according to a weight ratio, and continuing to stir and mix to obtain a slurry, and filtering the slurry to obtain component A;
[0017] 2) Preparation of component B:
[0018] (1) Mix the curing agent, dispersant, defoamer, adhesion promoter and solvent thoroughly and stir them evenly according to the weight ratio;
[0019] (2) adding the rheological additive to the mixed material in step (1) according to the weight ratio and continuing to stir and mix;
[0020] (3) adding mica powder, active pigment and zinc powder to the mixture in step (2) by weight, mixing and filtering to obtain component B;
[0021] 3) When using, mix the component A and the component B in proportion.
[0022] Preferably, when preparing component A, in step (1), the substances are mixed in proportion and then added to a dispersion kettle, and stirred at room temperature for 5-15 minutes; in step (2), the thickener is added and stirring is continued for 10-30 minutes;
[0023] When preparing component B, in step (1), the materials are mixed in proportion and then added to a dispersion kettle, and stirred at room temperature for 5-15 minutes; in step (2), the rheological additive is added and the stirring is continued for 10-30 minutes; in step (3), mica powder, active pigment and zinc powder are added and the stirring is continued for 30-60 minutes.
[0024] The zinc-ene coating provided by the present invention still has long-term protection capability after being damaged, adopts a new process, uses a hydrophilic polyamide curing agent as a carrier of zinc powder, and is pre-dispersed into zinc slurry, and cross-linked and cured with epoxy emulsion as a supporting component, which not only ensures the stability of zinc powder in liquid coating, but also ensures the corrosion resistance of the product, and prepares a two-component water-based epoxy zinc-ene coating with excellent comprehensive performance. The use of this coating can avoid the problems of construction inconvenience, dust pollution, and waste of zinc powder caused by adding zinc powder on site, and the comprehensive performance is comparable to that of solvent-based epoxy zinc-rich coating, and can completely replace solvent-based products; on the other hand, the pigment-to-base ratio of traditional water-based epoxy zinc-rich coating is relatively high, so the adhesion to metal substrates will be slightly worse than that of conventional baking varnish and other products. However, the water-soluble coating obtained by the present invention adds an appropriate amount of adhesion promoter, which is pre-dispersed and wetted with zinc powder to form a zinc paste. The purpose is to perform as much surface coating treatment on the zinc powder as possible, so that the coating is anchored between the metal substrate and the paint film and the active pigment through the principle of silane bridging during the film formation process, and the simple physical mixture originally formed between the inorganic filler and the organic resin is transformed into a more solid chemical bond, thereby increasing the cohesion of the coating. The final gain effect is that adding a small amount of adhesion promoter, combined with the preferred filler system, can form a synergistic effect, improve the adhesion between the coating and the substrate, and greatly extend the protection time of the coating to the substrate, that is, the corrosion resistance is significantly improved. Compared with the traditional method of adding epoxy phosphate or using modified curing agent to improve the overall adhesion of the system, this method greatly improves the secondary adhesion of the paint film after the salt spray test, and does not affect the stability of the coating system. It can even achieve a salt spray resistance time of more than 1500h and the corrosion spread at the scratch is within 0.5mm; in addition, the secondary adhesion of the coating to the substrate after the salt spray test is still very good, the coating is difficult to be peeled off, and the corrosion resistance is outstanding. Specific data are shown in the following examples, and it can be seen from the data that the performance of the water-based coating obtained by the present invention, especially the salt spray resistance and corrosion resistance, has reached or even exceeded the solvent-based zinc-rich coating with the same zinc content, which is very conducive to the water-based, environmentally friendly and low-VOC coating. DETAILED DESCRIPTION
[0025] The present invention will be further explained below in conjunction with specific implementation schemes, but the present invention is not limited thereto.
[0026] On one hand, the present invention provides a zinc-ene coating having long-term protective capability after being damaged, comprising: component A and component B, wherein the mass ratio of component A to component B is 1:2.5-4, component A comprises epoxy resin emulsion, thickener, wetting agent, defoamer, anti-flash rust agent, deionized water and graphene dispersion, component B comprises curing agent, adhesion promoter, dispersant, defoamer, rheological additive, mica powder, active pigment, zinc powder and solvent, and component A comprises, by weight: 70-80 parts of epoxy resin emulsion; Thickener 0.2-0.6 parts; wetting agent 0.1-0.4 parts; defoamer 0.1-0.4 parts; anti-flash rust agent 0.1-0.4 parts; deionized water 2-12 parts; graphene dispersion 10-25 parts; component B, by weight, includes: curing agent 3-6 parts; dispersant 1-1.5 parts; defoamer 0.1-0.4 parts; rheological additive 0.2-0.6 parts; mica powder 2-3 parts; active pigment 4-10 parts; zinc powder 70-80 parts; adhesion promoter 1-2 parts; solvent 4-12 parts.
[0027] The epoxy resin emulsion is one or more of an emulsion of the E-20 system, a self-emulsifying resin of the E-20 system, an emulsion of the E-51 system, and a self-emulsifying resin of the E-51 system; preferably, the epoxy resin emulsion is an epoxy resin emulsion of the E20 system, with a solid content of 52%, an epoxy equivalent of 500, and contains a small amount of cosolvent and deionized water.
[0028] The thickener is one or more of cellulose, hydrophobically modified acrylate, and polyurethane; preferably, the thickener is an associative polyurethane thickener, such as modified polyurethane, which can increase low shear viscosity, has little effect on gloss, and is insensitive to pH value.
[0029] The wetting agent is one or more of a surfactant, a low molecular weight siloxane-type surfactant, a fluorocarbon surfactant, and an acetylenic glycol; preferably, the wetting agent is a polyether-modified siloxane-type wetting agent, such as a low molecular weight polysiloxane. This type of wetting agent can quickly reduce the surface tension of the system, has excellent anti-shrinkage ability and will not stabilize foam, and has no effect on the recoating of the paint film.
[0030] The defoamer is one or more of natural oils and fats, polyether defoamers, high-carbon alcohol defoamers, silicone defoamers, polyether-modified silicone defoamers, and polysiloxane defoamers; preferably, the defoamer is a mixture of one or more of polyether type, silicone oil type, and polyether modified type, for example, polyether type such as glycerol, polyoxyethylene oxypropylene glycerol, etc. prepared by addition polymerization of propylene oxide or a mixture of ethylene oxide and propylene oxide; silicone oil type such as polydimethylsiloxane; polyether modified type such as polyether-siloxane copolymer. The use of defoamers can reduce surface tension, inhibit the generation of foam or eliminate the generated foam. Polyether modified defoamers have the advantages of both strong hydrophobicity and rapid bubble breaking, and are low in cost, small in dosage, and long in foam suppression time.
[0031] The flash rust preventer is one or more of sodium nitrite, sodium molybdate, strontium chromate, metal organic chelate, and multifunctional phosphate chelate; preferably, the flash rust preventer is a VOC-free nitrite and borate type flash rust preventer, such as sodium nitrite aqueous solution, because this flash rust preventer has no effect on other materials in the coating, does not affect the color of the paint film, and has a synergistic effect with the anti-corrosion pigment in the coating, and a very low dosage can provide excellent flash rust prevention performance.
[0032] The graphene dispersion is one or more of single-layer graphene, multi-layer graphene, oxidized graphene, hydrogenated graphene, and functionalized graphene; preferably, the graphene dispersion is a high-quality thin-layer graphene aqueous pre-dispersion, the effective component of which accounts for 10%, and the rest is solvent (water), and it contains a dispersant and a stabilizer to keep the graphene in the dispersion effectively dispersed and non-agglomerated. The unique sheet structure of graphene can form a "maze-like" structure with flaky powder, extend the diffusion path of the corrosive medium, and effectively improve the barrier and shielding properties of the coating; on the other hand, the conductive graphene and zinc powder will form an effective micro-conductive circulation path, thereby effectively ensuring that the zinc powder plays a protective role as an anode, improving the utilization rate of zinc powder, and extending the protection time of the coating on the metal substrate.
[0033] The curing agent is one or more of amidated polyamines, polyamides, and amine adducts; preferably, the curing agent is a water-soluble modified polyamide curing agent, such as a modified polyamide curing agent with an active hydrogen equivalent of 118, a solid content of 60%, and a solvent of PM or PMA. Because the zinc powder is added to component B, component B cannot contain water, and can fully wrap the zinc powder without reacting with the zinc powder.
[0034] The adhesion promoter is a mixture of one or more of silane coupling agent, acetylacetone, and organic-inorganic hybrid modified silane coupling agent. Silane coupling agent is very easy to hydrolyze. When it is added to the water-based coating system, it will quickly hydrolyze to generate a large number of silanol groups. The silanol groups dehydrate and condense to generate oligosiloxane containing silanol groups. The hydroxyl groups in the oligomer interact with the hydroxyl groups on the surface of the substrate to form hydrogen bonds. In this way, the silane coupling agent can connect the film-forming material at one end and the substrate at the other end, forming a "bridge" between the coating and the metal substrate, thereby improving the adhesion between the coating and the substrate. Therefore, the water resistance and salt water resistance of the coating are gradually improved with the increase of silane coupling agent until it is stable. At the same time, the rust diffusion width at the scratch is gradually reduced with the increase of silane coupling agent, which also proves the improvement of the corrosion resistance of the coating, that is, the improvement of the corrosion resistance of the coating.
[0035] The dispersant is one or more of anionic, cationic, nonionic, electrically neutral, and polymeric. Preferably, the dispersant is a block copolymer containing a pigment affinity group, such as a polyvinyl lactone polyol-polyethyleneimine block copolymer, a reaction product of polycaprolactone and triethylenetetramine, an acrylate polymer, and a polyacrylate. This type of dispersant can reduce the viscosity of the grinding material and stabilize it, has anti-floating ability, and is more suitable for an anti-corrosion and anti-rust coating system.
[0036] The rheological additive is one or more of organic bentonite, clay, castor oil derivatives, fumed silica, modified hydrogenated castor oil, N-methylpyrrolidone solution of modified polyurea, and polyamide wax; preferably, the rheological additive is one or more of organic bentonite, clay, fumed silica, and polyamide wax. The rheological additive is used because the specific gravity of zinc powder is very large, and it is easy to settle in the system, resulting in difficulty in stirring during use, and even forming a hard block at the bottom of the container, causing the coating system to demulsify and thus the coating to fail. In order to prevent the zinc powder from precipitating, the characteristics of bentonite with good suspension and dispersibility can be used to improve the stability of the coating suspension, so that it is not easy to delaminate. In addition, bentonite can form flocculent substances, which have a thickening effect, and its molecular groups can be combined with the organic base material in the coating to enhance the water resistance of the coating and improve the strength and adhesion of the coating. The surface of fumed silica contains siloxy groups and silanol groups, which have good affinity with film-forming substances and can interact to form hydrogen bonds. The anti-settling particles adsorbed with zinc powder can be stably suspended in the coating system. Polyamide wax has good compatibility and can improve the fluidity of the resin. After the coating is applied, it can migrate to the coating surface during the volatilization of solvents and water, and finally form a "waxed" surface with other components of the coating, enhancing the coating's wear resistance and extending the coating's salt spray resistance and acid and alkali immersion resistance time.
[0037] The mica powder is one or more of muscovite, sericite, and phlogopite with a mesh size between 100 and 1500; the special flaky structure of the mica powder can prolong the path of the corrosive medium invading the substrate and prolong the protection time of the coating on the substrate. Sericite is a monoclinic crystal with flaky crystals and block-shaped crystal aggregates with a silky luster. It has good dispersion and suspension properties in water media and organic solvents, is white and fine in color, is difficult to dissolve in acid and alkali solutions, has stable chemical properties, and effectively improves the anti-penetration, weather resistance, wear resistance and corrosion resistance of the coating. During the coating process, the sericite chips lie down under the action of surface tension before the paint film solidifies, and automatically form a structure that is parallel to each other and also parallel to the surface of the paint film. Such a layered arrangement is oriented perpendicular to the direction in which the corrosive substance penetrates the paint film, forming a "maze effect" for the corrosive medium and fully exerting the barrier effect.
[0038] The active pigment is one or more of super phosphorus zinc white, natural ferrophosphorus powder, polymerized ferrophosphorus powder, and ferrotitanium powder; the active pigment introduces a variety of anti-rust pigments (salts), and various components play to their strengths and avoid their weaknesses, and purposefully strengthen and improve the performance of the pigment itself. By utilizing the chelation of phosphate ions and metals, the addition of active ingredients solves the early "flash rust" phenomenon of the coating, greatly improving the anti-rust performance of the coating.
[0039] The zinc powder is one or more of spherical zinc powder and flaky zinc powder with a mesh size of 600 to 1200 and a purity of more than 95%; zinc powder is the key to realizing the anti-corrosion function of the anti-corrosion coating. Since the standard electrode potential of zinc powder is more negative than that of steel, when corrosive substances contact the metal substrate, the zinc powder is gradually dissolved to protect the steel; after the zinc powder is corroded and dissolved for a period of time, many zinc corrosion products such as zinc oxide, basic zinc carbonate, zinc phosphate, etc. are deposited between the zinc powder and the pigment and filler particles. These corrosion products are dense and non-conductive, filling the gaps between the pigment and filler layers, and can block the penetration of corrosive media, that is, in the later stage of corrosion, the protective layer formed by the corrosion products and the coating plays an anti-corrosion role.
[0040] The solvent is one or more of PM, DPM, PMA, and BCS. Preferably, the solvent is a mixed solvent of PM and DPM. PM and DPM have different volatilization rates. The drying time is adjusted during the drying and curing of the coating, that is, it is not too fast or too slow, so as to ensure that the paint film forms a dense coating during the drying process. At the same time, the use of an appropriate amount of DPM has a beneficial effect on the anti-corrosion performance of the coating.
[0041] The present invention also provides a method for preparing a zinc-ene coating having long-term protective capability after being damaged, comprising the following steps:
[0042] 1) Preparation of component A:
[0043] (1) According to the weight ratio, epoxy resin emulsion, defoamer, wetting agent, anti-rust agent, deionized water and graphene dispersion are fully mixed and stirred;
[0044] (2) adding a thickener to the mixture in step (1) according to a weight ratio, and continuing to stir and mix to obtain a slurry, and filtering the slurry to obtain component A;
[0045] 2) Preparation of component B:
[0046] (1) Mix the curing agent, dispersant, defoamer, adhesion promoter and solvent thoroughly and stir them evenly according to the weight ratio;
[0047] (2) adding the rheological additive to the mixed material in step (1) according to the weight ratio and continuing to stir and mix;
[0048] (3) adding mica powder, active pigment and zinc powder to the mixture in step (2) by weight, mixing and filtering to obtain component B;
[0049] 3) When using, mix the component A and the component B in proportion.
[0050] Wherein, when preparing component A, in step (1), the substances are mixed in proportion and then added to a dispersion kettle, and stirred at room temperature for 5-15 minutes; in step (2), the thickener is added and stirred for 10-30 minutes;
[0051] When preparing component B, in step (1), the materials are mixed in proportion and then added to a dispersion kettle, and stirred at room temperature for 5-15 minutes; in step (2), the rheological additive is added and the stirring is continued for 10-30 minutes; in step (3), mica powder, active pigment and zinc powder are added and the stirring is continued for 30-60 minutes.
[0052] Example 1
[0053] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoaming agent, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0054] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent, 1 part of adhesion promoter and 9.7 parts of solvent were mixed and stirred for 10 minutes, then 0.4 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 2.1 parts of mica powder, 8.6 parts of active pigment (ferrophosphorus powder) and 71.9 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0055] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0056] Example 2
[0057] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoaming agent, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0058] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent, 1 part of adhesion promoter and 9.7 parts of solvent were mixed and stirred for 10 minutes, followed by adding 0.4 parts of rheological additive and continuing to stir for 20 minutes, and finally adding 2.1 parts of mica powder, 8.6 parts of active pigment (super phosphorus zinc white) and 71.9 parts of zinc powder and continuing to stir for 30 minutes, and filtering to obtain component B.
[0059] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0060] Example 3
[0061] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoaming agent, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0062] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent, 1 part of adhesion promoter and 9.7 parts of solvent were mixed and stirred for 10 minutes, then 0.4 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 2.1 parts of mica powder, 8.6 parts of active pigment and 71.9 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0063] In specific use, 100 parts of component A and 250 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0064] Example 4
[0065] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoaming agent, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0066] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent, 1 part of adhesion promoter and 9.7 parts of solvent were mixed and stirred for 10 minutes, then 0.4 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 2.1 parts of mica powder, 8.6 parts of active pigment and 71.9 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0067] In specific use, 100 parts of component A and 400 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0068] Example 5
[0069] According to the weight ratio, 70 parts of epoxy resin emulsion, 0.1 parts of defoaming agent, 0.4 parts of wetting agent, 0.4 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.2 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0070] Then, according to the weight ratio, 3 parts of curing agent, 1 part of dispersant, 0.1 parts of defoaming agent, 2 parts of adhesion promoter and 12 parts of solvent were mixed and stirred for 10 minutes, then 0.2 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 2 parts of mica powder, 10 parts of active pigment and 70 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0071] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0072] Example 6
[0073] According to the weight ratio, 80 parts of epoxy resin emulsion, 0.1 parts of defoaming agent, 0.1 parts of wetting agent, 0.4 parts of anti-flash rust agent, 2 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.2 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0074] Then, according to the weight ratio, 6 parts of curing agent, 1.5 parts of dispersant, 0.1 parts of defoaming agent, 2 parts of adhesion promoter and 10 parts of solvent were mixed and stirred for 10 minutes, then 0.6 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 3 parts of mica powder, 10 parts of active pigment (ferrophosphorus powder) and 70 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0075] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0076] Example 7
[0077] According to the weight ratio, 70 parts of epoxy resin emulsion, 0.4 parts of defoaming agent, 0.4 parts of wetting agent, 0.1 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.2 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0078] Then, according to the weight ratio, 6 parts of curing agent, 1 part of dispersant, 0.3 parts of defoaming agent, 2 parts of adhesion promoter and 4 parts of solvent were mixed and stirred for 10 minutes, then 0.2 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 3 parts of mica powder, 4 parts of active pigment and 80 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0079] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature, and the zinc-ene coating is obtained after the mixture is evenly mixed.
[0080] Comparative Example 1
[0081] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoaming agent, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0082] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent and 10.7 parts of solvent were mixed and stirred for 10 minutes, followed by adding 0.4 parts of rheological additive and continuing to stir for 20 minutes, and finally adding 2.1 parts of mica powder, 8.6 parts of active pigment (ferrophosphorus powder) and 71.9 parts of zinc powder and continuing to stir for 30 minutes, and filtering to obtain component B.
[0083] When used specifically, 100 parts of component A and 300 parts of component B are mixed at room temperature according to weight ratio, and the mixture is evenly mixed to obtain zinc-ene coating.
[0084] Comparative Example 2
[0085] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoaming agent, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent, 12 parts of deionized water and 10 parts of graphene dispersion were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirring was continued for 20 minutes, and component A was obtained by filtering.
[0086] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent and 10.7 parts of solvent were mixed and stirred for 10 minutes, followed by adding 0.4 parts of rheological additive and continuing to stir for 20 minutes, and finally adding 2.1 parts of mica powder, 8.6 parts of active pigment (super phosphorus zinc white) and 71.9 parts of zinc powder and continuing to stir for 30 minutes, and filtering to obtain component B.
[0087] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature and mixed evenly to obtain the zinc-ene coating.
[0088] Comparative Example 3
[0089] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoamer, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent and 22 parts of deionized water were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirred for 20 minutes, and the mixture was filtered to obtain component A.
[0090] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent, 1 part of adhesion promoter and 9.7 parts of solvent were mixed and stirred for 10 minutes, then 0.4 parts of rheological additive were added and stirring was continued for 20 minutes, and finally 2.1 parts of mica powder, 8.6 parts of active pigment (ferrophosphorus powder) and 71.9 parts of zinc powder were added and stirring was continued for 30 minutes, and filtered to obtain component B.
[0091] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature and mixed evenly to obtain the zinc-ene coating.
[0092] Comparative Example 4
[0093] According to the weight ratio, 76.7 parts of epoxy resin emulsion, 0.3 parts of defoamer, 0.3 parts of wetting agent, 0.2 parts of anti-flash rust agent and 22 parts of deionized water were mixed and stirred for 10 minutes; 0.5 parts of thickener was added and stirred for 20 minutes, and the mixture was filtered to obtain component A.
[0094] Then, according to the weight ratio, 4.9 parts of curing agent, 1.1 parts of dispersant, 0.3 parts of defoaming agent, 1 part of adhesion promoter and 9.7 parts of solvent were mixed and stirred for 10 minutes, followed by adding 0.4 parts of rheological additive and continuing to stir for 20 minutes, and finally adding 2.1 parts of mica powder, 8.6 parts of active pigment (super phosphorus zinc white) and 71.9 parts of zinc powder and continuing to stir for 30 minutes, and filtering to obtain component B.
[0095] In specific use, 100 parts of component A and 300 parts of component B are mixed at room temperature and mixed evenly to obtain the zinc-ene coating.
[0096] Table 1 Differences in formulations of Examples 1-7 and Comparative Examples 1-4
[0097]
[0098] As mentioned above, the resin emulsion is an epoxy resin emulsion of E20 system with a solid content of 52% and an epoxy equivalent of 500 (commercially available product from Guangdong Tongde); the thickener is an associative polyurethane solution with a non-volatile content of 49% to 53% and a specific gravity of 1.04 (the solvent is ethylene glycol monobutyl ether and water); the defoamer is an organosilicon defoamer (commercially available product from AFCONA); the wetting agent is a polyether modified siloxane (commercially available product from AFCONA); the flash rust inhibitor is a 5% aqueous sodium nitrite solution; the graphene dispersion is a high-quality thin-layer graphene aqueous pre-dispersion, the effective ingredient of which accounts for 10%, and the rest is solvent (water).
[0099] The curing agent is a water-soluble modified polyamide curing agent with an active hydrogen equivalent of 118 and a solid content of 60 parts. The solvent is PM and PMA (a commercial product from Guangdong Tongde); the dispersant is a block copolymer containing pigment affinity groups with a molecular weight of 900, a non-volatile content of 80±5 parts, and a specific gravity of 1.1±0.05 (the main components are triethanolamine and alkyl ammonium salt) (a commercial product from Silok); the defoamer is an organosilicon defoamer (a commercial product from AFCONA); the solvent is PM and DPM (PM and DPM (v / v) = 1:1); the rheological additives are organic bentonite (commercially available product, from Zhejiang Hongyu) and polyamide wax (commercially available product, model 451); the mica powder is sericite with a mesh number between 300 mesh and 1500 mesh (commercially available product, from Anhui Ge Rui); the active pigment is super phosphorus zinc white or ferrophosphorus powder with a mesh number between 800 mesh and 1200 mesh (commercially available product, from Taihe Huijin); the zinc powder is spherical zinc powder with a mesh number between 600 mesh and 1200 mesh (commercially available product, from Jiangsu Shenlong); the adhesion promoter is a silane-type formula (model CX-2, from Shanghai Xiaogeng).
[0100] The zinc-ene coatings obtained in Examples 1-7 and Comparative Examples 1-4 were tested:
[0101] Airless spraying was used to spray 90-110 μm on a standard test carbon steel plate, and performance tests were performed after curing, including impact resistance, neutral salt spray resistance, water resistance, etc. (tests were performed according to the standard "HG / T3668-2020 Zinc-rich Primer"). The coating performance results of each embodiment are shown in Table 2.
[0102] Table 2 Coating dry film test performance table
[0103]
[0104] It can be seen from Table 2 that when only adhesion promoter or only graphene is used, the salt spray resistance time of the coating is not long, and the unidirectional corrosion expansion and stripping distance of the coating are relatively large. For example, when no adhesion promoter is used, the stripping distance of the coating is greater than the unidirectional corrosion expansion distance, indicating that the effect of the adhesion promoter is very obvious. It cannot play a role in resisting the spread of corrosion when it is not added. Therefore, the stripping distance of the coating is very large, 3.9mm and 7.7mm. When the active filler is used in conjunction with the adhesion promoter, the corrosion resistance of the coating is significantly enhanced. Among them, the unidirectional corrosion expansion results of the iron phosphate powder combined with the adhesion promoter meet the standard requirements (less than or equal to 2mm), and the stripping distance of the coating is also consistent with the unidirectional corrosion expansion, but the overall salt spray resistance time of the coating is not very long, only 800h; when the super phosphorus zinc white is used in conjunction with the adhesion promoter, the unidirectional corrosion expansion is consistent with the stripping distance of the coating, and the results are the smallest, only 0.5mm, and the salt spray resistance time of the coating can reach 1500h intact. It can be seen that the active filler super phosphorus zinc white, graphene and adhesion promoter have a synergistic effect, which makes the coating have excellent anti-corrosion propagation characteristics, and the coating can still provide effective protection to the substrate after being damaged.
[0105] Mix component A and component B, and apply the mixed coating by brushing, roller coating, airless spraying or air spraying on the surface of the steel substrate that has been sandblasted or polished in advance. The air spray can be diluted with a diluent (deionized water as a diluent) to make the thickness of the dried film reach 100±10μm, and use it as a primer. After that, it can be used in conjunction with a water-based epoxy micaceous iron intermediate paint and a water-based polyurethane topcoat or a water-based epoxy topcoat. The dried coating can protect the steel substrate very well. The zinc powder in the coating can release electrons to provide cathodic protection for the steel substrate at the damaged part of the coating. The rheological additive can help the zinc powder to be evenly dispersed and prevent the zinc powder from sinking to the surface of the steel substrate. The unique lamellar structure of graphene can form a "maze-like" structure with the flaky powder, extending the diffusion path of the corrosive medium and effectively improving the barrier and shielding properties of the coating. Adhesion promoters can form hydrogen bonds, transforming the simple physical mixing reaction originally formed between inorganic fillers and organic resins into stronger chemical bonds, increasing the cohesion of the coating. At the same time, the formation of hydrogen bonds can significantly improve the adhesion between the substrate and the entire coating, preventing further spread of corrosion.
[0106] When the active pigment is super phosphorus zinc white, the mechanism of action of the coating lies in the synergistic protective effect of super phosphorus zinc white, graphene and adhesion promoter. The role of graphene is mainly concentrated during the service period of the coating. After the bottom zinc powder in contact with the metal substrate at the damaged coating is consumed, the conductive effect of graphene allows the zinc powder above the coating in the vertical direction to continue to contact the substrate, and the zinc powder undergoes an anodic oxidation reaction, which plays a role of cathodic protection, greatly improving the utilization rate of zinc powder and inhibiting the spread of corrosive media to the metal substrate in the horizontal direction. The contribution of the adhesion promoter lies in the curing period of the coating. It improves the adhesion between the coating and the substrate, especially the maintenance of wet adhesion. After the coating is damaged, the coating around the damaged area can continue to maintain high adhesion, so that the corrosive medium cannot easily pass through here, delaying the spread of corrosion. This not only extends the service life of the coating, but also enhances the ability of the coating to resist the spread of corrosion.
[0107] In summary, it can be explained that the active pigment combined with the adhesion promoter can improve the salt spray resistance and corrosion resistance of the coating, so that the coating still has long-term protection after damage. Especially when the active pigment is super phosphorus zinc white, it can be significantly improved by combining it with the preferred adhesion promoter, so that the coating still has long-term protection after damage.
Claims
1. A zinc-ene coating having long-term protective capability after being damaged, characterized in that: include: Component A and component B, wherein the mass ratio of component A to component B is 1:2.5-4, component A comprises epoxy resin emulsion, thickener, wetting agent, defoamer, anti-flash rust agent, deionized water and graphene dispersion, component B comprises curing agent, adhesion promoter, dispersant, defoamer, rheological additive, mica powder, active pigment, zinc powder and solvent, and component A comprises, by weight: 70-80 parts of epoxy resin emulsion; 0.2-0.6 parts of thickener; 0.05 parts of wetting agent; .1-0.4 parts; defoamer 0.1-0.4 parts; anti-flash rust agent 0.1-0.4 parts; deionized water 2-12 parts; graphene dispersion 10-25 parts; component B, by weight, includes: curing agent 3-6 parts; dispersant 1-1.5 parts; defoamer 0.1-0.4 parts; rheological additive 0.2-0.6 parts; mica powder 2-3 parts; active pigment 4-10 parts; zinc powder 70-80 parts; adhesion promoter 1-2 parts; solvent 4-12 parts.
2. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The epoxy resin emulsion is one or more of an emulsion of an E-20 system, a self-emulsifying resin of an E-20 system, an emulsion of an E-51 system, and a self-emulsifying resin of an E-51 system; the thickener is one or more of cellulose, hydrophobic modified acrylate, and polyurethane; the wetting agent is one or more of a surfactant, a low molecular weight siloxane-type surfactant, a fluorocarbon surfactant, and an acetylene glycol.
3. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The defoaming agent is one or more of natural oils and fats, polyether defoaming agents, high-carbon alcohol defoaming agents, silicon defoaming agents, polyether-modified silicon defoaming agents, and polysiloxane defoaming agents; the anti-flash rust agent is one or more of sodium nitrite, sodium molybdate, strontium chromate, metal organic chelates, and multifunctional phosphate chelates.
4. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The graphene dispersion is one or more of single-layer graphene, multi-layer graphene, oxidized graphene, hydrogenated graphene, and functionalized graphene.
5. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The adhesion promoter is one or more of a silane coupling agent, acetylacetone, and an organic-inorganic hybrid modified silane coupling agent.
6. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The active pigment is one or more of super phosphorus zinc white, natural ferrophosphorus powder, polymerized ferrophosphorus powder, and iron-titanium powder.
7. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The curing agent is one or more of amidated polyamines, polyamides, and amine adducts; the dispersant is one or more of anionic, cationic, nonionic, electrically neutral, and polymeric; the rheological additive is one or more of organic bentonite, clay, castor oil derivatives, fumed silica, modified hydrogenated castor oil, modified polyurea N-methylpyrrolidone solution, and polyamide wax.
8. The zinc-ene coating having long-term protective capability after being damaged according to claim 1, characterized in that: The mica powder is one or more of muscovite, sericite, and phlogopite with a mesh size between 100 mesh and 1500 mesh; the zinc powder is one or more of spherical zinc powder and flaky zinc powder with a mesh size between 600 mesh and 1200 mesh and a purity of more than 95%; the solvent is one or more of PM, DPM, PMA, and BCS.
9. The method for preparing the zinc-ene coating having long-term protective capability after being damaged according to any one of claims 1 to 8, characterized in that: The steps include: 1) Preparation of component A: (1) According to the weight ratio, epoxy resin emulsion, defoamer, wetting agent, anti-rust agent, deionized water and graphene dispersion are fully mixed and stirred; (2) adding a thickener to the mixture in step (1) according to a weight ratio, and continuing to stir and mix to obtain a slurry, and filtering the slurry to obtain component A; 2) Preparation of component B: (1) Mix the curing agent, dispersant, defoamer, adhesion promoter and solvent thoroughly and stir them evenly according to the weight ratio; (2) adding the rheological additive to the mixed material in step (1) according to the weight ratio and continuing to stir and mix; (3) adding mica powder, active pigment and zinc powder to the mixture in step (2) by weight, mixing and filtering to obtain component B; 3) When using, mix the component A and the component B in proportion.
10. The method for preparing the zinc-ene coating having long-term protective capability after being damaged according to claim 9, characterized in that: When preparing component A, in step (1), the various substances are mixed in proportion and then added to a dispersion kettle, and stirred at room temperature for 5-15 minutes; in step (2), the thickener is added and stirred for 10-30 minutes; When preparing component B, in step (1), the materials are mixed in proportion and then added to a dispersion kettle, and stirred at room temperature for 5-15 minutes; in step (2), the rheological additive is added and the stirring is continued for 10-30 minutes; in step (3), mica powder, active pigment and zinc powder are added and the stirring is continued for 30-60 minutes.
Citation Information
Patent Citations
Water-based graphene zinc powder anticorrosive paint and preparation method thereof
CN114276707A
Water-based zinc-rich anticorrosive paint capable of resisting corrosion spreading and preparation method of water-based zinc-rich anticorrosive paint
CN116200096A